Expanding structural insights into DNA packaging apparatus and endolysin LysSA05 function of Epsilon15 bacteriophage - Khan, Muhammad Saleem Iqbal; Wu, Ju; Ji, Shenlin; Tan, Demeng; Sui, Bingrui; Peng, Shanshan; Zhan, Jinbiao; Yin, Jiajun (Frontiers in Cellular and Infection Microbiology, 2025)
The rising prevalence of multidrug-resistant (MDR) foodborne pathogens, particularly Salmonella spp., necessitates alternative antimicrobial solutions. Phage therapy offers a promising solution against MDR Gram-negative infections; however, its clinical application is constrained by the presence of endotoxins, residual cellular debris, the risk of horizontal gene transfer by temperate phages, and an incomplete understanding of how phage structural integrity influences infectivity and enzyme function. In this study, we present a structural and functional analysis of temperate bacteriophage Epsilon15 (ϵ15), focusing on its DNA packaging and injection machinery, along with characterization of the dual-acting endolysin LysSA05. Iodixanol-purified virions suspended in phosphate-buffered saline (PBS), under conditions optimized to preserve virion stability, were analyzed using graphene oxide (GO)-supported cryo-electron microscopy. This approach resolved the full asymmetric architecture of ϵ15, revealing a detailed internal nucleic acid organization with at least eight concentric layers radially and approximately 28 axially compacted layers within the capsid. The DNA packaging machinery, comprising the core, portal, and hub, was resolved at high resolution, including a 42 nm-long and 18 nm-wide injection channel anchored by a dodecameric portal complex visualized at 7 Å resolution. Concurrently, we characterized LysSA05, a dual-acting endolysin harboring a glycoside hydrolase 19 (GH19) catalytic domain accommodating peptidoglycan (PG) residues N-acetylmuramic acid (NAM) and N-acetylglucosamine (NAG) through structural docking, indicating plausible binding interactions that promote hydrolysis support vector machine (SVM), random forest (RF), discriminant analysis (DA), artificial neural network (ANN) and physicochemical scanning identified an amphipathic helix (residues 59-112) with predicted antimicrobial peptide (AMP)-like properties. Biochemical validation confirmed that LysSA05 destabilizes lipopolysaccharides (LPS) and permeabilizes the outer membrane of Gram-negative bacteria independently of permeabilizers, with enhanced efficacy observed upon co-treatment with Ethylenediaminetetraacetic acid (EDTA) or citric acid. In summary, our findings elucidate key structural features of ϵ15 relevant to infection and genome delivery, while positioning LysSA05 as a promising enzybiotic candidate against MDR Gram-negative pathogens.